Stereotactic radiosurgery alone for brain arteriovenous malformations: a single-institute experience - Zhao-Ying Zhu; Wei Zhang; Shi-Hong Zhu; Gui-Jun Zhang; Jing Chen (BMC Neurology, 2024)
Abstract Objective Brain arteriovenous malformations (BAVMs) represent an ongoing clinical challenge because of their complex nature. The long-term outcomes of BAVMs patients treated with stereotactic radiosurgery (SRS) alone are unclear. Methods We conducted a retrospective analysis of 201 patients treated for BAVMs from January 2010 to December 2019. The identified predictors of obliteration or hemorrhage in the multivariate analysis were estimated by odds ratios (ORs) with 95% confidence intervals (CIs). Results A total of 201 patients treated with gamma knife radiosurgery (GKRS) alone as the primary treatment for BAVMs were included. The mean age at GKRS treatment was 31.4 ± 1.1 years, and 61.2% of the patients were male. Multivariate logistic regression revealed that a higher radiosurgery-based AVM score (OR 1.847, 95% CI = 1.292–2.641; p = 0.001) was significantly associated with worse obliteration, and a higher margin dose significantly favored obliteration (OR 0.352, 95% CI = 0.189–0.658; p = 0.001). Multivariate analysis revealed that an increased lesion volume of 1 cm3 (OR 1.279, 95% CI = 1.023–1.600; p = 0.031) and a high margin dose (OR 0.363, 95% CI = 0.134–0.983; p = 0.046) were significant prognostic factors for post-SRS hemorrhage. Conclusions In conclusion, our study investigated the available clinical and radiological prognostic factors for BAVMs and revealed that a higher margin dose significantly improved both the obliteration rate and nonhemorrhagic outcomes. Currently, the most appropriate candidates, Spetzler-Martin grade, and optimal radiation dose are still being defined by prospective trials.